The Effect of Product Completeness, Service and Store Location on Consumer Purchase Interest (Case Study at Bukupena Kartasura Store) - Widia Priatna; Agus Suyatno; Indra Hastuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find the effect of product completeness on consumer buying interest, the effect of service on consumer buying interest and the effect of store location on consumer buying interest at Bukupena Kartasura. The method used is a quantitative research method with simple linear regression analysis using a Likert scale in the SPSS version 26 software application. The results of the study conclude that the product completeness variable simultaneously influences consumer buying interest, service variables have a positive effect on consumer buying interest and store location. has a positive effect on consumer buying interest at Bukupena Kartasura Store so that these three variables most influence consumer repurchase intention for products sold at Bukupena Kartasura Store